Middle East and North Africa Quarterly Economic Brief, January 2014 : Growth Slowdown Heightens the Need for Reforms - Devarajan, Shantayanan; Mottaghi, Lili (Washington, DC: World Bank, 2014)
Ongoing regional tensions, together with a challenging (albeit slightly improving) external environment, have hit the economies of the Middle East and North Africa (MENA) region hard. Economic growth is slowing, fiscal buffers are depleting, unemployment is rising, and inflation is mounting in seven of the region’s most vulnerable economies-- Egypt, Tunisia, Iran, Lebanon, Jordan, Yemen and Libya. Short-term policy actions such as increasing public sector wages and subsidies—aimed at reducing social tensions--exacerbate the situation, which is driven by long-standing structural weaknesses, including labor market rigidities, complicated and opaque regulations, infrastructure deficiencies, regressive and inefficient subsidies, and inadequate social safety nets. While these countries face an unstable political and macroeconomic environment, the growth slowdown after the Arab Spring creates a unique opportunity to address these structural problems to both create fiscal space and restructure the economy towards job creation and inclusive growth.